APOBEC3B Nuclear Localization Requires Two Distinct N-Terminal Domain Surfaces. Issue 17 (17th August 2018) - Salamango, Daniel J.; McCann, Jennifer L.; Demir, Özlem; Brown, William L.; Amaro, Rommie E.; Harris, Reuben S.
Abstract: The APOBEC3 family of cytosine deaminases catalyzes the conversion of cytosines-to-uracils in single-stranded DNA. Traditionally, these enzymes are associated with antiviral immunity and restriction of DNA-based pathogens. However, a role for these enzymes in tumor evolution and metastatic disease has also become evident. The primary APOBEC3 candidate in cancer mutagenesis is APOBEC3B (A3B) for three reasons: (1) A3B mRNA is upregulated in several different cancers, (2) A3B expression and mutational loads correlate with poor clinical outcomes, and (3) A3B is the only family member known to be constitutively nuclear. Previous studies have mapped non-canonical A3B nuclear localization determinants to a single surface-exposed patch within the N-terminal domain (NTD). Here, we show that A3B has an additional, distinct, surface-exposed NTD region that contributes to nuclear localization. Disruption of residues within the first 30 amino acids of A3B (import surface 1) or loop 5/α-helix 3 (import surface 2) completely abolish nuclear localization. These import determinants also graft into NTDs of related family members and mediate re-localization from cell-wide-to-nucleus or cytoplasm-to-nucleus. These findings demonstrate that both sets of residues are required for non-canonical A3B nuclear localization and describe unique surfaces that may serve as novel therapeutic targets. Graphical Abstract: Unlabelled Image Highlights: How is the viral and genomic mutagen APOBEC3B imported into the nucleus? Nuclear localization of APOBEC3B requires two distinct surfaces. Residues from APOBEC3B relocalize APOBEC3D from whole cell to nucleus. Residues from APOBEC3B relocalize APOBEC3F from cytoplasm to nucleus. The import surfaces described here could serve as novel therapeutic targets.